1993
DOI: 10.1093/jn/123.5.926
|View full text |Cite
|
Sign up to set email alerts
|

A Depletion-Repletion Folate Bioassay Based on Growth and Tissue Folate Concentrations of Rats

Abstract: To improve standardization of a folate bioassay, folate-depleted rats were repleted with a folate-free amino acid-based diet supplemented with 29 levels of folic acid. Growth was the main response variable and body tissue folate concentrations were also assessed. Because a positive correlation was observed between low levels of dietary folic acid and growth and little or no correlation was observed between high levels and growth, six regression models with a steep slope for low levels and a shallow or zero slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Parallel to the observed decrease in plasma folate, we detected an increase in plasma homocysteine (60% increase at 8 months, P < .001). Folate deficiency caused a moderate but not significant growth retardation of 14% in wild-type mice ( P =.17) and 5.3% in Ung −/− mice ( P = .50), which correlates with previous studies (see Supplementary Figure 1 and Table 1 online at at www.gastrojournal.org)31.…”
Section: Resultssupporting
confidence: 90%
“…Parallel to the observed decrease in plasma folate, we detected an increase in plasma homocysteine (60% increase at 8 months, P < .001). Folate deficiency caused a moderate but not significant growth retardation of 14% in wild-type mice ( P =.17) and 5.3% in Ung −/− mice ( P = .50), which correlates with previous studies (see Supplementary Figure 1 and Table 1 online at at www.gastrojournal.org)31.…”
Section: Resultssupporting
confidence: 90%
“…When general nutritional status was studied, we observed that supplementation with folic acid did not affect normal growth in rats. This is in accordance with other studies in which folate-enriched diets did not improve growth response (Clifford et al 1993;Alonso-Aperte, 1997). As expected, pregnant rats had a higher FER when compared with virgin rats, but folic acid level in the diet did not influence FER.…”
Section: Discussionsupporting
confidence: 93%
“…Both diets were adjusted to rat requirements (National Research Council, 1995), and were based on the pure amino acid diet (170 g amino acid/kg, Dyets, Bethlehem, PA, USA) described by Walzem & Clifford (1988). This is the most reliable system for studying the exclusive effect of dietary folic acid, without confounding factors, as demonstrated in several previous studies (Walzem & Clifford, 1988;Clifford et al 1989Clifford et al , 1993Varela-Moreiras & Selhub, 1992;Varela-Moreiras et al 1995b;Alonso-Aperte & Varela-Moreiras, 1996).…”
Section: Animals and Dietsmentioning
confidence: 99%
“…However, Clifford et al and Birn et al have shown that the absence of dietary folate and B 12 readily reduces tissue levels of both vitamins in most nonbony organs, such as liver, kidney, heart, lungs, and others, within 4-8 wk. (41)(42)(43)(44) Based on these data, there is no reason to believe that the time of intervention (12 wk) was insufficient in this study. However, Clifford et al and Birn et al did not measure bone levels of folate and B 12 .…”
Section: Discussionmentioning
confidence: 97%